Relevansi Ajaran Hidup Sastra Wulangreh Pada Etnis Jawa Mataram Kepanjen Kabupaten Malang - Nurwakhid Muliyono (IKIP Budi Utomo Malang, 2017)
Literary works created by writers to be enjoyed, understood, and utilized by the community by using language as a medium. Literature is a language essay on socio-cultural issues in the form of getting positive judgments from the public. The use of the mystical language of the palace was able to penetrate far geographical location to rural and mountainous areas. Social, cultural and political factors led them to mesanggrah and alienated into the area of Brang Wetan commonly known Mataraman region. Majority, Kepanjen society is Java Mataraman estany which still holds closely to ancestral tradition. Some forms of local wisdom are still carried out today, one of them is Serat Wulangreh written by Sri Susuhunan Paku Buwono IV in Surakarta Hadiningrat In the government of 1788-1820. Javanese people are very concerned about the teachings in Fiber Wulangreh and practiced in everyday life. Wulangreh fiber is a characteristic of Indonesian culture that has high literary value, aesthetics, education and philosophy. In Fiber Wulangreh there is a living doctrine: Understanding the sense of life, sharpening the inner eye, avoiding the arrogant attitude, the duty of the living, the filial piety, and the service to the king. These teachings became guidance and guidance for the Javanese ethnic community Mataraman Kepanjen, the community has consistently preserved until now. Therefore, this phenomenon is very interesting to be careful because this phenomenon occurs in a society that is experiencing changes in all aspects (social, cultural, economic, and globalization). Based on the above description, this paper will describe: (a) how is Fiber Wulangreh practiced as a moral and intellectual teaching (b) how is Serat Wulangreh practiced as a living doctrine, and (c) how is the relevance of Wulangreh literary life teaching to ethnic Javanese mataram in Kepanjen Malang Regency. This qualitative research involves the active participation of researchers on the object of the study. Interviews conducted by researchers to obtain data on various matters related to Fiber Wulangreh Data analysis of village monograph in the analysis with qualitative descriptive method to what extent Fiat Wulangreh live and grow in society.